Aiding sleep in type 2 diabetes: therapeutic considerations. Issue 1 (January 2018) - Tan, Xiao; van Egmond, Lieve; Chapman, Colin D; Cedernaes, Jonathan; Benedict, Christian
Summary: Insomnia and obstructive sleep apnoea (OSA) are more prevalent in patients with type 2 diabetes than in the general population. Both insomnia and OSA have been linked to cardiometabolic alterations (eg, hypertension, increased activity of the sympathetic nervous system, and systemic insulin resistance) that can exacerbate the pathophysiology of type 2 diabetes. Improvement of sleep in patients with diabetes could therefore aid the treatment of diabetes. To help health practitioners choose the best clinical tool to improve their patients' sleep without detrimentally affecting glucose regulation, this Review critically analyses the effects of common treatments for insomnia and OSA on both sleep and glucose metabolism in patients with type 2 diabetes. These treatments include pharmaceutical sleep aids (eg, benzodiazepine receptor agonists, melatonin) and cognitive behavioural therapy for insomnia, continuous positive airway pressure for OSA, and lifestyle interventions.